Characteristics of Senior High School Students in the Utilization of School Library in Indonesia - Harisanti, Dessy; Putri Anugrah, Esti (International Journal of Engineering and Technology, 2018)
School library provides various facilities and services adjusted to the needs of students as library users. With the availability of various facilities and services in the school library, the students can choose the facilities and library services that want to be utilized to meet their needs in the school environment. This study aims to determine the characteristics of students in the utilization of school library. This research uses quantitative approach with descriptive analysis. The location of this research is in a library of a Senior High School (SMA) in Surabaya, the second largest city in Indonesia.Â  The results of this study indicate that high school students in the use of school libraries have different characteristics. They more often visit the library during break time compared to other times. Students use the library for school work, and some students do other activities in the library. In the case of borrowing books, the students mostly only borrow one book, the borrowed book is in Bahasa Indonesia, and not many students borrow collections in foreign languages. From this research, it can also be seen that many collections that do not fit between the bookshelves and the catalog / OPAC. Thus, it makes the students prefer to search directly on the shelf instead of using the catalog / OPAC. On the other hand, it is also because the students are still confused in using OPAC.Â Â